2008
DOI: 10.1111/j.1468-3083.2008.02637.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of adverse drug reactions: guidelines

Abstract: Knowledge of adverse drug-induced oral effects helps health professionals to better diagnose oral disease, administer drugs and improve patient compliance during drug therapy and may foster a more rational use of drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 50 publications
(55 reference statements)
0
61
0
5
Order By: Relevance
“…Our patients' sali vary phosphorus and sIgA were significantly diminished, which might be due to hyposalivation or malnutrition [14]. Our patients' BMI was signifi cantly lower than that of the controls, reflecting a possible malnutrition state as shown by Vaidyanathan [15], who reported a very high prevalence of malnutrition among patients with CHD.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Our patients' sali vary phosphorus and sIgA were significantly diminished, which might be due to hyposalivation or malnutrition [14]. Our patients' BMI was signifi cantly lower than that of the controls, reflecting a possible malnutrition state as shown by Vaidyanathan [15], who reported a very high prevalence of malnutrition among patients with CHD.…”
Section: Discussionmentioning
confidence: 48%
“…Chew reviewed the anticholinergic activity of 107 medications such as cardiovascular agents, of which digoxin, furosemide, and enalapril were commonly used by our patients [13]. The anticholinergic activity of medications are exerted via sever al routes: a competition with acetylcholine at effector junction, and an indirect effect through stimulation of sympathetic system [14]. In accordance with our results, Hegde et al [7] noticed that salivary pH and flow rate were significantly decreased in cardiac patients, which was associated with the level of salivary sialic acid; hence, it was proposed that sialic acid would be a good indicator for the severity of oral disease in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A single intrauterine exposure to a drug can affect the fetal structures undergoing rapid development at the time of exposure (Koren, 2007). Knowledge of adverse drug-induced oral effects helps health professionals to better diagnose oral disease, administer drugs and improve patient compliance (Femiano et al, 2008). Cappon and co-workers, in their study, did not find any teratogenic effect of Aspirin in rabbits even when large doses were administered on single day during specific windows of development (Cappon et al, 2003) however, teratogenicity of aspirin has been reported at high doses in rodents (Berry & Nickols, 1979).…”
Section: Introductionmentioning
confidence: 92%
“…Tardive dyskinesias (TDK) are persistent, involuntary abnormal movements that can involve the face, head, neck, limbs and trunk . Orobuccofacial dyskinesias, which are dyskinesias involving the face, mandible, lips and tongue, are often the first manifestation of TDK and the most common form.…”
Section: Drug‐induced Tardive Dyskinesiamentioning
confidence: 99%